2020
DOI: 10.1097/mou.0000000000000772
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in neuroimaging of bladder, bowel and sexual function

Abstract: Purpose of review In this review, we summarize recent advances in the understanding of the neural control of the bladder, bowel and sexual function, in both men and women. Recent findings Evidence of supraspinal areas controlling the storage of urine and micturition in animals, such as the pontine micturition centre, emerged in the early 20th century. Neurological stimulation and lesion studies in humans provided additional indirect evidence for additional bladder-related brain areas. Thereafter, functional ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Among these, the first study was performed using SPECT, and it revealed activation at the upper pons, left sensorimotor cortex, right frontal cortex, and bilateral somatosensory cortex during bladder filling in healthy volunteers [36]. These findings were consistently reproduced by PET and fMRI using more advanced visuo-mathematical analysis tools; in addition, the activation in the PAG, cerebellum, thalamus, basal ganglia, insular cortex (IC), anterior cingulate (ACG), and prefrontal cortex are consistently observed [37][38][39][40][41][42][43] (Fig. 3A).…”
Section: Neuroimaging Studies Relevant To Lut Functionmentioning
confidence: 92%
“…Among these, the first study was performed using SPECT, and it revealed activation at the upper pons, left sensorimotor cortex, right frontal cortex, and bilateral somatosensory cortex during bladder filling in healthy volunteers [36]. These findings were consistently reproduced by PET and fMRI using more advanced visuo-mathematical analysis tools; in addition, the activation in the PAG, cerebellum, thalamus, basal ganglia, insular cortex (IC), anterior cingulate (ACG), and prefrontal cortex are consistently observed [37][38][39][40][41][42][43] (Fig. 3A).…”
Section: Neuroimaging Studies Relevant To Lut Functionmentioning
confidence: 92%
“…The insula monitors bladder sensory information and, when necessary, shifts our attention to our bladder so that we can look for an appropriate time and place to initiate voiding. These higher level processes and the ultimate decision to void require frontal cortex activity ( Gao et al, 2015 ; Coolen et al, 2020 ; Locke et al, 2022 ). These cortical and subcortical structures are likely to exercise their control over the LUT via the PAG.…”
Section: Introductionmentioning
confidence: 99%